(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Objective: The main objective of the Stability-indicating method is to monitor results during stability studies to guarantee quality, safety, and efficacy. Thus, the present study is mainly focused on developing a simple, accurate, rapid, and economic stability-indicating assay method for the determination of the Lenvatinib drug by the RP-HPLC method.